Pemanfaatan Batu Sungai Matang Kabupaten Enrekang pada Laston Lapis Antara - Skolastiko Patinggi; Alpius; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2023)
In the develompment of road construction and repair, it is necessary to aptimize it to support the welfare of the community, especially in Enrekang Regency which has the potential for producing materials in the form of aggregate or Matang River stone which according to him has never been used for road pavement. This study aims to determine the characteristics of the Matang River aggregate, ehat is the proportion of the AC-BC micture after carrying out the Conventional Marshall test and ehat are the result of the remaining Marshall Stbility (SMS) on the AC-BC mixture. The result of the study, the characteristics origanating from the Matang River have met the 2018 Bina Marga Spesification. According to the design of the AC-BC mixture, the coarse aggregate is 42.45%, the fine aggregate is 45.18%, the filler is 5.36% with an aptimum asphalt content of 7,00%. The Marshall immersion Stability value on the AC-BC mixture using Matang River aggregate meets the 2018 Highways Spesifications Division 6, which is 93.31% > 90%.